Finite element analysis of the effect of cantilever and implant length on stress distribution in an implant-supported fixed prosthesis - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1996)
This study investigated the stress distribution at the bone/implant interface with a three-dimensional finite element stress analysis by using three different cantilever and implant lengths in an implant-supported fixed partial denture, Simulation models were created as a bilateral distal cantilever fixed partial denture supported with six implants embedded in a model of the mandibular bone, Nine different simulation models had three different cantilevers (7, 14, and 28 mm) and implant lengths (7, 15, and 20 mm), Vertical forces of 75 N and horizontal forces of 25 N were applied to the distal end of the cantilever, Analysis of the von Mises stresses for the bone/implant interfaces revealed that the maximum stresses occurred at the most distal bone/implant interface located on the loaded side and significantly increased with the length of the cantilever. However, there was no statistically significant change associated with the length of implants.
Keywords: ENDOSSEOUS IMPLANTS; DENTAL IMPLANTS